Study of "Mathematical Anxiety" in Students of the Precalculus Course at the Latin American University of Science and Technology and the General Mathematics Course at the Costa Rica Institute of Technology in the First Quarter of 2023: Estudio de la “ansiedad matemática” en estudiantes del curso de Precálculo de la Universidad Latinoamericana de Ciencia y Tecnología y del curso de Matemática General del Tecnológico de Costa Rica en el I Cuatrimestre de 2023 - Castro Méndez, Didier (2025)
Mathematics anxiety is a common phenomenon that negatively affects students' academic performance. The main objective of this study was to evaluate the level of mathematical anxiety in Precalculus students of the Universidad Latinoamericana de Ciencia y Tecnología (ULACIT) and General Mathematics of the Tecnológico de Costa Rica (TEC) during the first period of 2023. In addition, we sought to determine if there are differences in the level of anxiety by sex and educational center. The research was of a descriptive quantitative type. The sample consisted of 905 students enrolled in the aforementioned courses, who were administered a validated questionnaire to measure mathematics anxiety. Student's t-test was used to analyze differences by sex and educational center. The results reveal that 19.01% exhibit high levels of anxiety and women present a higher level of mathematical anxiety compared to men. In addition, no differences were detected in the level of mathematical anxiety according to educational center.